QUALITY OF WASTE WATER AND POLLUTED AIR GALVANIC-CHEMICAL PROCESSES - Arsenović, B.; Ivanović, B. (Journal of Engineering & Processing Management, 2016)
The process of galvanic-chemical protection according to the qualitative and quantitative characteristics, is one of the most complex wastewater pollutants. Also, from the surfaces of industrial solutions, as well as the protected parts of the stages of care, there are significant fumes, which pollute the surrounding air, which is to be treated prior to discharge into the environment. Depending the way they emerged, wastewater contains: the free acids and bases; specific contaminants: cyanide, chromium and nitrate and dissolved heavy metals: Fe, Cd, Ni, Cu, Zn, Ag, etc. Polluted air is full with mixed vapors of acids and bases, as well as the specific chromium and cyanide vapors. The paper shows the procedures, as well as, mechanisms of treatment of wastewater and poluted air generated in the process of galvanicchemical protection in the collective of "Orao" JSC for production and overhaul Bijeljina. The results obtained were compared with the values prescribed by regulations in the Republic of Srpska in the field of waste water and emissions of air pollutants.